Penerapan RESTful API untuk Membangun Program Pembayaran Piutang Menggunakan Otentikasi OAuth 2.0 - Nina Wulandari; Argo Wibowo; Budi Susanto (Jurnal Terapan Teknologi Informasi, 2021)
Retail business competition which is increasingly fast requires businesses to have a product sales strategy that is able to compete. Amigo Group convert this strategy by providing account receivable services for customers. The study " Penerapan RESTful API untuk Membangun Program Pembayaran Piutang Menggunakan Otentikasi OAuth 2.0", focused on how to use RESTful to provide the transaction API for accounts receivable payments, and the use of OAuth 2.0 as an authentication method, as well as load testing of API. The system design has been done with UML modeling language in the form of activity diagrams and sequence diagrams. Programming was done using the Laravel framework and MySQL database. Load testing was performed using the Locust application. These designs produced Back End functions that can be used on web and mobile platforms. As a result of load testing, the use of the OAuth 2.0 method is more advantageous than using Basic Auth. This is shown by the response time and request per second which is more stable in the use of OAuth 2.0.